OŚWIĘCIM, CHEAP BREAD, AND POTATOES IN THE WOUNDS: POLAND IN THE EYES OF CHINESE POETS. - Krenz, Joanna (Porównania, 2019)
The paper analyzes representations of Poland in contemporary Chinese poetry. The author sketches the beginnings of the poetic dialogue between China and Poland which date back to the early 20th century and the history of these interactions until the late 1980s to focus subsequently on three works written after the year 1989: Yi Ping’s “Oświęcim, Spring, and Resurrection”, Wang Jiaxin’s “On the German-Polish Border”, and Lei Pingyang’s “Poems from Poland”. The reflection centers not as much on how the Chinese poets depict Poland as on what these images tell of the Chinese poets themselves. The Poland that emerges from their writings is an alternative space in which they can safely engage in discussions concerning their own history and tradition, settling with the mistakes, myths, and utopias of China’s cultural past.